A Survey: Wireless Sensor Networks - Umashankar, M. (IJRDO -Journal of Computer Science Engineering, 2017)
Wireless sensor networks consists of inexpensive sensor nodes, each node has continuous sensing capability with limited communication power. They can be used for several applications such as commercial, civil, and military applications including vehicle tracking, climate monitoring, intelligence, medical, agriculture, etc. Their deployment in environments disaster areas, earthquake/rubble zones or in military battlegrounds can be seriously affected by any kind of sensor failure or malicious attack/security threats from an enemy. The amount of power carried by the sensor itself is very limited; replacing sensor or sensor battery is a very time-consuming and costly process, in certain application environment. Energy efficient operation, channel contention, latency, management, and security of such networks are complex and critical issues that have to be addressed.